Plasma electrolytic oxidation coatings with fungicidal properties*. (3rd April 2019) - Pezzato, Luca; Cerchier, Pietrogiovanni; Brunelli, Katya; Bartolozzi, Alessandra; Bertani, Roberta; Dabalà, Manuele
ABSTRACT: Plasma electrolytic oxidation (PEO) is a relatively new surface treatment that permits to increase the corrosion and wear resistance of metals. One of the peculiarities of the process is the possibility to incorporate into the produced coating the particles suspended in the electrolyte. In this work, micrometric silver particles were added in the PEO coating to innovatively give a fungicidal effect to the samples due to the presence of silver, whose fungicidal effect is well known. PEO coatings were produced on aluminium alloy 7075 using an electrolyte containing sodium silicate and silver particles. The thickness, morphology, composition and corrosion resistance of the obtained coatings were studied. The fungicidal properties were evaluated with contact tests of 2 and 4 h using Candida albicans ATCC 10231. Silver particles were homogeneously distributed in the coating and the silver-containing samples were characterised by improved corrosion resistance and high fungicidal activity.